2021
DOI: 10.3390/ijerph18189427
|View full text |Cite
|
Sign up to set email alerts
|

Users’ Intention to Continue Using Online Mental Health Communities: Empowerment Theory Perspective

Abstract: Introduction: Online mental health communities may provide new opportunities for rehabilitation for people with mental illness, so it is important to understand the factors that influence the continued use of online mental health communities by people with mental illness. Methods: From the perspective of empowerment, based on the theory of health self-efficacy and expectation confirmation, this study explored the mediating role of health self-efficacy and expectation confirmation in the empowerment process of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
11
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 25 publications
(13 citation statements)
references
References 69 publications
2
11
0
Order By: Relevance
“…Patients' extent of confirmation significantly affected both perceived usefulness (β=.817; P<.001) and satisfaction (β=.61; P<.001). These findings are consistent with the original ECM as well as the findings of previous research on information system usage (eg, telemedicine and health data reporting platform usage) among patients [32][33][34][35]. The confirmation of patients' expectations has a positive effect on perceived usefulness and satisfaction, and the improvement of perceived usefulness and satisfaction can further enhance patients' enthusiasm for continuing to use a system.…”
Section: Summary Of Findingssupporting
confidence: 89%
“…Patients' extent of confirmation significantly affected both perceived usefulness (β=.817; P<.001) and satisfaction (β=.61; P<.001). These findings are consistent with the original ECM as well as the findings of previous research on information system usage (eg, telemedicine and health data reporting platform usage) among patients [32][33][34][35]. The confirmation of patients' expectations has a positive effect on perceived usefulness and satisfaction, and the improvement of perceived usefulness and satisfaction can further enhance patients' enthusiasm for continuing to use a system.…”
Section: Summary Of Findingssupporting
confidence: 89%
“…Patients need to sift through this information to find a physician who meets and trusts their needs, which can be quite a troubling process for patients [ 6 ]. Online health communities utilize various methods to alleviate problems such as selection and service evaluation and build trust between doctors and patients [ 7 ]. Existing studies have identified several factors that influence patient choice, including patient factors, such as patient ratings [ 8 ], and physician factors, such as physician title [ 9 ], service attitudes, and the number of online reviews [ 10 ].…”
Section: Introductionmentioning
confidence: 99%
“…The online medical and health community is the main platform for providing online consultation services, where users disseminate, obtain, use, and evaluate health [1][2][3]. Such a powerful interactive platform has a positive impact on patients' daily disease control, self-health management, and emotional support [4][5][6]. However, the convenience of internet services and trust in online health information may affect users' search behavior [7].…”
Section: Introductionmentioning
confidence: 99%